Interest as a mode of reality: Answering the crisis of digital society - Novri Susan; Doddy Sumbodo Singgih (Masyarakat, Kebudayaan dan Politik, 2023)
Currently, society is entering a new crisis in the historical phase of society namely post-truth reality. The crisis arises when the mixing of real and fake information is reproduced through social media by the digital actors. It has put new problems of social analysis particularly to understand the meaning and direction of social actions. This article aims at answering the crisis of the digital society with the elaboration of theoretical discourse of interest. Social scientists from various schools have placed interest as the basic concept to analyze social life. However, the sociological elaboration of the theory of interest stops among the great edifices of all schools of social theory. Therefore, this article is a proposal for developing a theory of interest to track the mode of reality, particularly in the digital society. The research method of this study is an eclectic literature review of interest theories and participative observation in Indonesia’s digital society during 2019-2021. This study finds that digital actors produce and reproduce symbolic language on social media by confounding true and false information or post-truth in the dynamics of the COVID-19 pandemic policy. The symbolic language of digital actors does not only mean violating the rules in a digital society, but also expresses certain social interests including certain needs or aspirations.